Pakistan as a nuclear power: Nuclear risks, regional conflicts and the dominant role of the military - Oliver Thränert; Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2009)
Amongst the nuclear powers, Pakistan is the most unstable state. This study mainly focuses on the following three research questions:1. How secure are Pakistan's nuclear weapons as well as its nuclear facilities? 2.How stable is the domestic political situation in Pakistan? 3.What are the perspectives for the ongoing Pakistan-India conflict? In recent years, Pakistan undertook numerous technical programs to secure its nuclear weapons arsenal. As far as is publicly known, these activities adequately secured the respective sites against non-authorized access. The Pakistani Army, which is responsible for the security of the nuclear weapons, is aware of their strategic and global value. Therefore, it can be expected to continue to do its best to secure Pakistan's nuclear arsenal. The USA on its part will pursue its current course of close nuclear cooperation with the Pakistani Army. Nonetheless, the security of the Pakistani nuclear weapons still is precarious, mainly due to the instability of the Pakistani society
Keywords: 320